The rationality of retirement preservation decisions: A conceptual model - Reyers, Michelle; ., Daniël Gerhardus Gouws (Journal of Economics and Behavioral Studies, 2014)
Low retirement savings rates, coupled with a lack of preservation of retirement funds when individuals move jobs, could have adverse repercussions on a person’s ability to retire with sufficient funds. The traditional response to low preservation levels has been to impose taxes on cash withdrawals and in some cases to mandate preservation. However, without a complete understanding of the factors that drive low levels of preservation, these policy interventions might do more harm than good. This study carries out a critical, interdisciplinary literature review to construct a conceptual model of the factors which potentially lead to low preservation levels and outlines proposed interventions. The resultant model highlights the distinct differences in the drivers of rational and irrational behaviour and therefore, the distinctly different interventions required. Little is known about the rationality or otherwise of the decision making process of individuals in the retirement preservation context, however current interventions only assist if individuals display bounded willpower. It is essential that a better understanding of the decision making process is obtained to determine whether existing solutions address the problem adequately.